Rallus nanus nomen novum: a replacement name for Rallus minutus Alcover et al. 2015 - Alcover, Josep Antoni; Pieper, Harald; Pereira, Fernando; Rando, Juan Carlos (Zootaxa, 2016)
In a recent paper, we described five new species of rails from the Macaronesian islands (Alcover et al., 2015). We proposed the name of Rallus minutus to designate the São Jorge rail. One day after its publication, Fred Ruhe (via e-mail) pointed out to us that the name was preoccupied, making Rallus minutus Alcover, Pieper, Pereira & Rando 2015 a primary homonym, which in turn makes it permanently invalid.